Representation of Ideological Education in the Nusantara Fiction - Rudi Umar Susanto; Fifi Khoirul Fitriyah (Linguistic, English Education and Art (LEEA) Journal, 2020)
The purpose of this research is to describe the Form of Ideology in Nusantara Folk Fiction Issued by the Ministry of Education and Culture in 2016. This study uses a qualitative interpretive approach with a parallel reading approach. The method is used to describe and interpret ideological representations in the 2016 Folk Archipelago Fiction published by the Ministry of Education and Culture in 2016. Data collection used in research is documentation technique, reading technique, and note taking technique. In this study produced two discussions, the form of ideology that can be used as an educational tool, and the ideological structure contained in the folklore of the archipelago. The forms contained are, among others, nationalist ideology and social ideology. In this connection, the two ideologies provide a foothold in this story. Moreover, nationalist values ​​and social values ​​that make a difference from other literary works. While for the ideological structure of this archipelago folklore, it is found that the ideological structure includes, Nationalists that lead to identity, and social which leads to social democracy. Keywords: Children's Literature,Nusantara People's Fiction,Ideology Education.